Automated rubber seed clones identification using QTR-1A reflectance sensor and PIC - Mustaffa, Nor Anida (2012)
This paper studies automated rubber seed clones identification using Reflectance sensors by create an intelligent and simple technology using application of Microcontroller PIC16F877A. There are five types of clones from the same species of rubber seed have been used as samples in this paper which are RRIM2002, RRIM2015, RRIM2020, RRIM2023 and RRIM2024. There three sensor reflectance (QTR-1A) was used to ensure that all surface samples taken the reading. Every surface reflects differently of light. The device measure the percentages of reflectance based on the intensity of light reflected from the seed surface. The Microsoft Office Excel was used to analysis the average voltage that converts from light reflectance of wavelength by takes 25 samples readings from 5 difference clones. Analysis results showed the average voltage derived from the data and graph; there are small differences in voltage for each type of clone. Finally, the range of average output voltage for each clone has been made based on the analysis obtained. It was found that there are the brightness of brown colour at front surface can be used in order to classify the types of rubber tree clones compare with back surface.